2015
DOI: 10.1002/jcb.25296
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of PHLDA1 Expression by JAK2-ERK1/2-STAT3 Signaling Pathway

Abstract: Toll-like receptor 2 (TLR2)-mediated signaling cascades and gene regulation are mainly involved in diseases, such as immunity and inflammation. In this study, microarray analysis was performed using bone marrow-derived macrophages (BMDM) and Raw 264.7 cells to identify novel proteins involved in the TLR2-mediated cellular response. We found that pleckstrin homology-like domain family, member 1 (PHLDA1) is a novel gene up-regulated by TLR2 stimulation and determined the unique signaling pathway for its expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 31 publications
1
9
0
1
Order By: Relevance
“…Moreover, STAT3 activation was inhibited by suppressing ERK1/2 signal during phenotype transition of macrophages. Our data, together with previous studies indicating that STAT3 may serve as the downstream signal of ERK1/2, 48,49 suggest that ERK1/2-STAT3 pathway is the molecular cue responsible for HA-mediated TAM formation. Based on these results, we conclude that macrophages within breast tumor microenvironment transform to M2 cells through HA-CD44-ERK1/2-STAT3 pathway that may be valuable as a target in suppressing TAM formation.…”
Section: Discussionsupporting
confidence: 83%
“…Moreover, STAT3 activation was inhibited by suppressing ERK1/2 signal during phenotype transition of macrophages. Our data, together with previous studies indicating that STAT3 may serve as the downstream signal of ERK1/2, 48,49 suggest that ERK1/2-STAT3 pathway is the molecular cue responsible for HA-mediated TAM formation. Based on these results, we conclude that macrophages within breast tumor microenvironment transform to M2 cells through HA-CD44-ERK1/2-STAT3 pathway that may be valuable as a target in suppressing TAM formation.…”
Section: Discussionsupporting
confidence: 83%
“…4e and Supplementary Table 5), including inhibitor of DNA binding 1 ( Id1; expressed by tissue-resident macrophages 28 ) and growth differentiation factor-15 ( Gdf15 ), which has been reported to drive expression of CCR2 in macrophages 29 . Further, significantly higher gene expression in airway AMs was observed for Toll like receptor (TLR)-induced inflammatory responses such as Polo-like kinase 3 ( Plk3 ) 30 and Pleckstrin homology like domain, family A, member 1 ( Phlda1 ) 31 and the cholesterol–trafficking START domain containing 9 ( Stard9 ) genes. Genes significantly higher in airway AMs from infected mice compared to uninfected mice demonstrated significant enrichment for pathways associated with metabolic pathways, antigen processing and phagocytosis (Supplementary Table 6).…”
Section: Resultsmentioning
confidence: 99%
“…TLRs are non-catalytic receptors characteristically expressed on innate immune cells such as macrophages and dendritic cells, and play important roles in the immune system though recognition of non-self matter [16]. The TLR2-mediated signaling pathway is mainly involved in inflammatory reactions, such as lung contusion [15].…”
Section: Phlda1 Promoted Lung Contusion Via Tlr2 Signaling Pathwaymentioning
confidence: 99%
“…The TLR2-mediated signaling pathway is mainly involved in inflammatory reactions, such as lung contusion [15]. Lyu et al showed that TLR2 stimulation could increase PHLDA1 expression via the JAK2-ERK1/2-STAT3 signaling pathway [16], indicating a relationship between TLR2 and PHLDA1. We investigated if PHLDA1 promoted lung contusion by regulating the TLR2 signaling pathway.…”
Section: Phlda1 Promoted Lung Contusion Via Tlr2 Signaling Pathwaymentioning
confidence: 99%